2013
DOI: 10.1063/1.4827099
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and theoretical study of the electronic spectrum of HPS, a second row HNO analog

Abstract: The à (1)A" - X (1)A' electronic spectra of jet-cooled HPS and DPS have been observed for the first time, using a pulsed discharge jet source. Laser induced fluorescence spectra were obtained in the 850-650 nm region. Although the 0(0)(0) band was not observed, strong 3(0)(n) and 2(0)(1)3(0)(n) progressions and 3(1) hot bands could be assigned in the HPS LIF spectrum. Single vibronic level emission spectra were also recorded, resulting in the determination of all three HPS ground state vibrational frequencies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 38 publications
(42 reference statements)
3
22
0
Order By: Relevance
“…For HPS, the likely state involved is A 1 A , which correlates with a 1 i state in the linear limit. 24 As this expression suggests, the nuclear spin-rotation parameters should be proportional to the respective rotational constants, if the second-order effect dominates. The C aa , C bb , and C cc constants for HPS have the values of 0.701 MHz, 0.0371, and 0.0091 MHz, respectively, which closely correlate with the rotational constants A 0 = 264,001 (36), B 0 = 8,379.1510 (22), and C 0 = 8,111.2313 (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For HPS, the likely state involved is A 1 A , which correlates with a 1 i state in the linear limit. 24 As this expression suggests, the nuclear spin-rotation parameters should be proportional to the respective rotational constants, if the second-order effect dominates. The C aa , C bb , and C cc constants for HPS have the values of 0.701 MHz, 0.0371, and 0.0091 MHz, respectively, which closely correlate with the rotational constants A 0 = 264,001 (36), B 0 = 8,379.1510 (22), and C 0 = 8,111.2313 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Theà 1 A −X 1 A electronic transitions of HPS and DPS have also been measured very recently using laser-induced fluorescence and single vibronic level emission spectroscopy. 24 Here we report the first measurements of the pure rotational spectrum of HPS and its D and 34 S isotopologues from microwave to submillimeter wavelengths. Both direct absorption and Fourier transform methods were employed in this study, as well as high-level quantum-chemical calculations, which assisted in the experimental investigation.…”
Section: Introductionmentioning
confidence: 94%
“…Very recently, Grimminger et al have reported thẽ A 1 A −X 1 A laser induced fluorescence (LIF) and singlevibronic-level (SVL) emission spectra of HPS and DPS. 1 In order to assist spectral assignments, density functional theory (DFT) calculations, and both single-reference (SR) and multi-reference (MR) ab initio calculations were carried out. 1 In addition, anharmonic Franck-Condon factors (FCFs) between the two states involved were computed with a "quick and dirty" approach (their quotes; see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…1 In order to assist spectral assignments, density functional theory (DFT) calculations, and both single-reference (SR) and multi-reference (MR) ab initio calculations were carried out. 1 In addition, anharmonic Franck-Condon factors (FCFs) between the two states involved were computed with a "quick and dirty" approach (their quotes; see Ref. 1 for details), employing computed coupled-cluster single and double plus perturbative triples {CCSD(T)} and complete active space self-consistent field multi-reference configuration interaction (including Davidson corrections) (CASSCF/MRCI) potential energy functions (PEFs) for the two electronic states, respectively, using the augmented correlation consistent polarized valence quadruple-zeta {aug-cc-pV(Q+d)Z} basis set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation